The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bcab.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and optimization of biosurfactant production by an oil-degrading Acinetobacter junii B6 isolated from an Iranian oil excavation site

Abstract: Isolation, characterization, and optimization of biosurfactant production by an oildegrading Acinetobacter junii B6 isolated from an Iranian oil excavation site, Biocatalysis and Agricultural Biotechnology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 57 publications
2
38
0
1
Order By: Relevance
“…The emulsification of ILCO observed in this study was 51%. Hence, it can be concluded that this biosurfactant has ability to play important role in bioremediation . The production of biosurfactant by A. baumannii MN3 was reported for degradation of crude oil at pH 7 and temperature 40 °C.…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 98%
See 2 more Smart Citations
“…The emulsification of ILCO observed in this study was 51%. Hence, it can be concluded that this biosurfactant has ability to play important role in bioremediation . The production of biosurfactant by A. baumannii MN3 was reported for degradation of crude oil at pH 7 and temperature 40 °C.…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 98%
“…Rhamnolipids synthesized by A. junii BD has great potential in microbial enhanced oil recovery (MEOR) because of its properties like interfacial surface reduction, wettability, and alteration . Ohadi et al studied the properties of biosurfactant produced by A. junii B6 and concluded that this biosurfactant has potential application in enhanced oil recovery process .…”
Section: Applications Of Biosurfactants Produced By Acinetobacter Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosurfactants are comparatively nontoxic and biodegradable products with unique properties such as superior foaming ability, high selectivity and active under adverse environmental conditions of pH, temperatures and salinity (Varjani and Upasani 2017). The microbial biosurfactants are amphipathic in nature with hydrophobic and hydrophilic regions that permit them to partition at the interface between immiscible liquid phases with diverse polarities such as oil and water (Ohadi et al 2017). Based on the origin and chemical nature, the biosurfactants are largely classified as lipopeptides, lipoproteins, glycolipids, phospholipids, fatty acids and polymeric molecules (Varjani and Upasani 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1 Biosurfactants comprise a wide variety of structurally distinct amphipathic molecules with potential applications in a wide range of biomedical fields, such as gene delivery, 7 antimicrobial, 8,9 anticancer, 10 and wound healing activities. [11][12][13] According to chemical structures, biosurfactants are categorized into two main groups; the lipopeptides and the glycolipids. 14 In nature, microemulsions formed using biosurfactant are thermodynamically stable and their isotropic systems are considered to be very promising in the development for DDS.…”
Section: Introductionmentioning
confidence: 99%